Development of a measurement of doctor-patient communication quality scale - Shao, Jiayi; Wen, Minhui; Zhang, Yuqing; Zhang, Liping; Sun, Jiangjie (Frontiers in Public Health, 2025)
BackgroundThe number of medical disputes in China has been increasing, highlighting the urgent need to improve doctor-patient relationships.ObjectiveTo improve doctor-patient relationships and enhance communication, a scale for measuring doctor-patient communication quality (DPCQ) was developed.MethodsBased on existing relevant foreign scales, questionnaire items were designed to collect patients' perceptions of doctor-patient communication quality. Outpatients from a selected hospital were chosen as the study population, and 300 questionnaires were randomly sampled. SPSS 26 was used for preliminary item screening through dispersion trend analysis, t-tests, and Pearson correlation analysis. Exploratory factor analysis (EFA) was conducted to assess the reliability of the questionnaire. Structural validity was examined using structural equation modeling (SEM) in R 4.4.3. Convergent and discriminant validity were evaluated using average variance extracted (AVE), composite reliability (CR), and maximum shared variance (MSV).ResultsThe EFA identified two factors: Factor 1 (Interactive Communication and Emotional Support) and Factor 2 (Health Education and Behavioral Guidance), with a cumulative variance contribution rate of 63.81%. The results of the CFA indicated an acceptable model fit: χ2/df = 3.57, AGFI = 0.837, RMSEA = 0.093, CFI = 0.945, NFI = 0.926, PGFI = 0.609, and PNFI = 0.733. The final version of the questionnaire demonstrated excellent internal consistency, with a Cronbach's α coefficient of 0.950. In addition, AVE exceeded the threshold of 0.50, CR values were greater than 0.70, and MSV for each factor was lower than its corresponding AVE, supporting both convergent and discriminant validity of the scale.ConclusionThe scale for measuring doctor-patient communication quality demonstrates good reliability and validity, making it a suitable measurement tool for research on doctor-patient communication.